2020
DOI: 10.3389/fvets.2020.00310
|View full text |Cite
|
Sign up to set email alerts
|

Histological, Immunological, and Genetic Analysis of Feline Chronic Gingivostomatitis

Abstract: Feline chronic gingivostomatitis (FCGS) is an immune-mediated inflammatory condition affecting the oral mucosa that results in substantial pain and suffering. The goal of this study was to complete an in-depth immunohistochemistry analysis of affected FCGS mucosa, to perform and compare immune cell phenotypes in the blood of FCGS and healthy controls cats, and to determine a transcriptomic profile of the affected and normal oral mucosa of FCGS cats. We hypothesized that cats with FCGS would have circulating ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
41
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 33 publications
6
41
1
2
Order By: Relevance
“…Histopathological results show a lymphoplasmacytic infiltrate, indicative of the chronic inflammatory process. Polyclonal hypergammaglobulinemia is also a consistent finding [ 1 , 6 , 7 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Histopathological results show a lymphoplasmacytic infiltrate, indicative of the chronic inflammatory process. Polyclonal hypergammaglobulinemia is also a consistent finding [ 1 , 6 , 7 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 80%
“…FCGS is considered multifactorial, although recent evidence suggests a T-cell disfunction [ 12 ], related to infectious and non-infectious causes, such as viruses, dental plaque, hypersensitivity reactions, environment conditions and stress in multi-cat households [ 6 , 7 , 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. With regards to viral agents, feline calicivirus (FCV) appears to carry out a relevant role in FCGS, three times more prevalent in these animals when compared to the general cat population [ 2 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,[13][14][15] The etiology of CGS is elusive and the pathogenesis is characterized by inappropriate immune response to an unknown antigenic stimulus, although underlying viral and bacterial etiologies have been proposed, including feline immunodeficiency virus (FIV), feline leukemia virus (FeLV), and feline calicivirus. 16,17 In order to re-evaluate the previously proposed risk factors and to investigate further potential risk factors, including oral inflammation, we performed an observational epidemiological case-control study on cats with confirmed OSCC. Results were compared with an age-matched random sample of client-owned healthy cats and with 2 groups of cats having, respectively, CGS and PD.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The predominance of CD8+ T cells within FCGS lesions suggests that the inflammation might be caused by a viral infection. 9,10 The possibility of respective associations between FCGS and multiple infectious agents, including FCV, FeLV, FIV, feline herpesvirus type 1, and Bartonella spp, has been investigated. 11-23,a,b Despite evidence suggesting a possible association between FCV and FCGS, results of multiple studies 12-16,18,19,21,23,24,a,b are inconsistent, and the role of FCV in FCGS remains uncertain.…”
mentioning
confidence: 99%